Case Report: A Novel Use of an Externalised Bi-Paddled PMMC Flap in Recurrent Buccal Mucosa Squamous Cell Carcinoma Reconstruction - ramesh, Ajay; Chandrasekar, Ajay (Journal of Neonatal Surgery, 2025)
Reconstruction after wide local excision (WLE) and segmental mandibulectomy in recurrent oral squamous cell carcinoma (SCC) poses distinct challenges in patients with previous surgeries and radiation. This report describes an innovative use of an externalised bi-paddled pectoralis major myocutaneous (PMMC) flap for buccal mucosa reconstruction in a medically and financially constrained patient with prior neck dissection and adjuvant therapy.